Knowledge translation strategies for policy and action focused on sexual, reproductive, maternal, newborn, child and adolescent health and well-being: a rapid scoping review. Issue 1 (17th January 2022) - Curran, Janet A; Gallant, Allyson J; Wong, Helen; Shin, Hwayeon Danielle; Urquhart, Robin; Kontak, Julia; Wozney, Lori; Boulos, Leah; Bhutta, Zulfiqar; Langlois, Etienne V
Abstract : Objective: The aim of this study was to identify knowledge translation (KT) strategies aimed at improving sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) and well-being. Design: Rapid scoping review. Search strategy: A comprehensive and peer-reviewed search strategy was developed and applied to four electronic databases: MEDLINE ALL, Embase, CINAHL and Web of Science. Additional searches of grey literature were conducted to identify KT strategies aimed at supporting SRMNCAH. KT strategies and policies published in English from January 2000 to May 2020 onwards were eligible for inclusion. Results: Only 4% of included 90 studies were conducted in low-income countries with the majority (52%) conducted in high-income countries. Studies primarily focused on maternal newborn or child health and well-being. Education (81%), including staff workshops and education modules, was the most commonly identified intervention component from the KT interventions. Low-income and middle-income countries were more likely to include civil society organisations, government and policymakers as stakeholders compared with high-income countries. Reported barriers to KT strategies included limited resources and time constraints, while enablers included stakeholder involvement throughout the KT process. Conclusion: We identified a number of gaps among KT strategies for SRMNCAH policy and action, including limited focus on adolescent, sexual and reproductive health and rights and SRMNCAH financing strategies. There is a need to support stakeholder engagement in KT interventions across the continuum of SRMNCAH services. Researchers and policymakers should consider enhancing efforts to work with multisectoral stakeholders to implement future KT strategies and policies to address SRMNCAH priorities. Registration: The rapid scoping review protocol was registered on Open Science Framework on 16 June 2020 (https://osf.io/xpf2k ).